PSIKOLINGUISTIK PEMBELAJARAN HURUF HIJAIYAH: ASOSIASI KATA (BERBASIS KLU) DAN DAYA INGAT ANAK USIA DINI - Muhammad Arifin Ilham; Tatang (Jurnal Bastra (Bahasa dan Sastra), 2025)
This study discusses the application of clue-based word association methods in the learning of hijaiyah letters for early childhood, specifically ages 4-5 years. The purpose of the research is to explore the influence of word-based clues on children's memory in recognizing hijaiyah letters and to identify the psycholinguistic factors that affect the success of the learning process. The research uses a descriptive qualitative approach with observational techniques at a tutoring center for learning hijaiyah letters. The research results show that the use of clues based on familiar words, such as "bakso" for the letter ص (sho) and "soto" for the letter ط (tho), significantly enhances children's memory. Older children (5 years old) tend to understand letters more quickly compared to 4-year-olds, indicating the influence of cognitive development on learning. However, certain less familiar letters, such as ض (do), are still difficult for some children to remember. This finding highlights the importance of the relevance of clues to the child's experience for effective learning.